1996
DOI: 10.1002/pro.5560050222
|View full text |Cite
|
Sign up to set email alerts
|

On the role of surface tension in the stabilization of globular proteins

Abstract: The stabilization of proteins by a variety of co-solvents can be related to their property of increasing the surface tension of water. It is demonstrated that, during the thermal unfolding of proteins, this increase of the surface tension can be overcome by the increase in the temperature of the solution at the midpoint of the transition, T,, and the weak binding of co-solvent molecules. Three such co-solvents were studied: trehalose, lysine hydrochloride (LysHCl), and arginine hydrochloride (ArgHC1). Trehalos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
198
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(214 citation statements)
references
References 41 publications
13
198
2
1
Order By: Relevance
“…13,30 The preferential hydration mechanism proposes that sugars are excluded from the environment around the protein and are replaced by water. 13,30,41 The preferential exclusion mechanism is supported by the increase in surface tension of water surrounding the protein due to the addition of sugars. 13,30,41 However, the exact reason for the enhanced structural stabilization of proteins in the presence of sugars is still unclear.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13,30 The preferential hydration mechanism proposes that sugars are excluded from the environment around the protein and are replaced by water. 13,30,41 The preferential exclusion mechanism is supported by the increase in surface tension of water surrounding the protein due to the addition of sugars. 13,30,41 However, the exact reason for the enhanced structural stabilization of proteins in the presence of sugars is still unclear.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Timasheff and coworkers [31,32] have developed a theory explaining the protein stabilisation effect, induced by the presence of detergents, being related to a preferential exclusion mechanism. Another theory considers the amphiphile nature of detergents.…”
mentioning
confidence: 99%
“…The stability of the native state of dissolved proteins is generally not affected by the presence of L-arginine. Earlier it was reported that L-arginine has been found to destabilize RNaseA [13] and Cytochrome C [14] slightly. On the other hand, Reddy et al (2005) hardly found any destabilizing effect of L-arginine.HCl up to concentrations level of 1.0 M in the case of hen egg white Lysozyme [15].…”
Section: Introductionmentioning
confidence: 94%